Relationship of soil physical and chemical properties with ecological species groups in Pinus taeda plantation in northern Iran - MOHAMMAD NAGHI ADEL; MEHRDAD GHODSKHAH DARYAEI; MOHADDESEH SEDIGHI PASHAKI; JAVAD JALALI; JAVAD SADEGH KUHESTANI; ROGHAYEH JIROUDNEZHAD (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Adel MN, Daryaei MG, Pashaki MS, JalaliJ, KuhestaniJS, Jiroudnezhad R. 2017. Relationship of soil physical and chemical properties with ecological species groups in Pinus taeda plantation in northern Iran. Biodiversitas 18: 422-426. The aim of this study was to investigate the relationship of physical and chemical properties of soils with ecological species groups in Pinus taeda plantation forests in Guilan province, Iran. For this purpose, a random systematic 100 m Ã— 200 m grid sampling plan was used to establish 75 sampling plots. In each plot, soil factors and percent cover of each herbaceous species were recorded. Sub-plots of 32 m2 were used for herbaceous species measurements. At each sampling plot, soil samples were collected in depth of 0-30cm. The result of TWINSPAN analysis revealed five dictinct groups. Multivariate analysis was performed through CANOCO 4.5 to explore the relationship between soil factors and plant community. Results showed that the most important soil factors in these communities were N, P, K, OC, Ca, Mg, TNV, pH, SP, soil texture (clay, sand, silt) and EC. The results indicated that the physical and chemical soil characteristics have a significant role in the growth and distribution of plant communities in the study area. Keywords: Pinus taeda, plantation, soil properties, vegetation